New flavors from old wheats: exploring the aroma profiles and sensory attributes of local Mediterranean wheat landraces - Frankin, Sivan; Cna'ani, Alon; Bonfil, David J.; Tzin, Vered; Nashef, Kamal; Degen, Doron; Simhon, Yasmin; Baizerman, Marina; Ibba, Maria Itria; González Santoyo, Héctor Ignacio; Luna, Cyntia Velazquez; Cervantes Lopez, Jose Fausto; et al. (Frontiers in Nutrition, 2023)
During the 20th century, the worldwide genetic diversity of wheat was sharply eroded by continual selection for high yields and industry demands for particular standardized qualities. A collection of Israeli and Palestinian landraces (IPLR) was established to represent genetic diversity, accumulated for ten millennia under diverse environments, which was mostly lost in this transition. As our long-term goal is to study this pre- Green Revolution genetic reservoir, herein we focus on its flour and bread quality and sensorial attributes. Initially, a database was built for the entire IPLR collection (n=901) holding both Triticum durum (durum wheat) and T. aestivum (bread wheat) which included genetic and phenotypic characterization of agronomic traits, grain and flour quality. Then, a representative subset of the IPLR was selected and compared to modern varieties for dough quality, rheology, aroma and taste using both whole and refined flours and breads. The sensory panel used 40 subjects who evaluated common protocol or sourdough breads made by four artisan bakers. Results show modern durum line ‘C-9’ had superior rheological properties (gluten index, elasticity, dough development time) as compared with landraces, while bread landrace ‘Diar Alla’ was markedly preferable for baking in relation to the modern cultivar ‘Gadish’. Baking tests and subsequent sensory evaluation clearly demonstrated a preference towards refined breads, apart from whole breads prepared using sourdough starters. In bread wheat, loaves baked using landrace flour were scored higher in several quality parameters, whereas in durum lines, the opposite trend was evident. Loaves baked from landraces ‘Diar Alla’ and to a lesser extent ‘Hittia Soada’ presented a markedly different aroma from the control loaves prepared from modern flours, both in terms of overall compositions and individual compounds, including classes such as pyranones, pyrazines, furans and pyrroles (maltol). Modern lines, on the other hand, were consistently richer in terpenes and phenylpropanoids. Further analysis demonstrated a significant association between specific aroma classes and sensory attributes scored by panelists. The findings of the study may help advance new niches in the local wheat market aimed at health and nutrition including adapting durum varieties to the bread market and developing flavor-enhanced wholemeal breads.